Analysis of the VP6 gene of human and porcine group A rotavirus strains with unusual subgroup specificities - Aksara Thongprachum (2018)
Full-length VP6 amino acid sequences of human and porcine rotaviruses with subgroup (SG) (I + II) and SG non-(I + II) were analyzed in comparison with those of SG I and SG II. In human rotaviruses, the strains in the same SG shared a very high degree of amino acid identity, ranging from 97.4% to 99.4% for SG I, 95.9% to 100% for SG II, and 99.4% to 100% for SG non-(I + II), while viruses in different SGs shared somewhat lower sequence identity at 90.4-93.1%. Conserved amino acids that distinguished the strains of SG I from SG II were observed at 21 positions. The viruses with SG non-(I + II) shared sequence identity with SG II as high as 97.2-99.7%, suggesting that they belonged to genogroup II. Similarly, porcine rotaviruses in the same SG shared 96.4-99.7% for SG I, 98.2-100% for SG II, 97.4-100% for SG (I + II), and 96.2-99.7% for SG non-(I + II), while strains in different SGs shared sequence identity ranging from 91.9% to 94.4%. Interestingly, the strains with SG (I + II) and SG non-(I + II) shared a high degree of sequence identity with SG I, at 96.4-100% and 94.7-99.7% respectively, suggesting that they are related to porcine SG I strains. The conserved amino acids which distinguished SG I from SG II were observed at 13 positions. The strains with SG I, SG (I + II), and SG non-(I + II) showed identical amino acid residues at these positions. Phylogenetic analysis strongly supported the findings of the sequence analysis. © 2008 Wiley-Liss, Inc.